Coastal ecosystem valuation as a tool for sustainable planning in Maputo - Beja da Costa, Ana (2021)
Many of the large urban areas of Africa are located along the coast, as is the case of Accra, Lagos, Luanda, Cape Town and Maputo, placing them both by their colonial origin and by its geographical context in a category of large cities that have a particular and strong relationship with their landscape setting, similar to places such as Mumbai, Rio de Janeiro and Hong Kong. Nature and urbanity are in extremely close proximity, with both spectacular and problematic results (Beja da Costa et al., 2009). In these cities, urban sprawl often occupies structuring and risk prone places of their ecological structures, namely proximity to flood plains and to vulnerable coastlines. Additionally, climate change and sea level rise introduce another dimension to the risk, (Tucci, 2009) that must be considered while planning these cities’ coastal areas. Focusing on Maputo, Mozambique, this paper will analyse an African capital that faces many development pressures, and where most development projects are targeting its coastline. This one is formed by both valuable and vulnerable landscapes in terms of visual quality and in terms of the quality of the natural resources and ecosystems value, given the variety of environments such as swamps, dunes and alluvium deposits, (Oliveira et al., 1996) that allow for the existence of a variety of biotopes. In turn, these play important roles for both the territory and the local population, given the value of the environmental setting as a direct food source, as a flood and hazard control mechanism and as a biodiversity asset to the city (which presents further economic gains for the city). This paper firstly presents an overall review regarding Maputo’s current urban planning processes; secondly it describes the specific ecological values of Maputo within its broader ecoregion context. The study proposes to analyse the valuation of ecosystem services of Maputo’s coastal landscapes, centred on the belief that there are greater benefits in retaining natural habitats than converting them into plantations, shrimp farms, etc. (de Groot, 2005) or into urban areas. It questions if the incorporation of ecosystem services may become a strategy towards the improvement of sustainable planning of the city’s coastal areas. The themes of ecosystem values and sustainability are to be addressed regarding a shift in Maputo’s urban development paradigm, aiming at safeguarding its natural systems while contributing to maintaining the city’s well-known image of quality